2021
DOI: 10.4018/ijlis.20210701.oa4
|View full text |Cite
|
Sign up to set email alerts
|

Extending TAM to Understand Library User Acceptance of E-Books in Tanzania

Abstract: This study was conducted to examine antecedents that influence acceptance of e-books in Tanzania. The study extended TAM model with accessibility, perceived cost, and technological support to develop a conceptual model that was used to examine acceptance of e-books in Tanzania. Quantitative study was conducted using self-administered questionnaire in which snowball technique was used to identify potential respondents. The questionnaires were distributed using online Google form, and 314 usable responses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…In accordance with the above, it is evident that there are more researchers who have used Subjective Norm, for example [59], [78], [82], [83], [1], [26], [85], [86], [87], [88], [89], [90], [91], [92], Experience in the internet & computer [59], [77], [81], [82], [84], [85], [93], [94], [95], [96], [97] Self-Efficacy [59], [83], [84], [85], [1], [71], [72], [73], [86], [95], [98], [99], [74], [97], Technical Support [59], [42], [73], [74], [83], [100], [101], [102] and Anxiety [72], [73],…”
Section: External Variables Of Tammentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance with the above, it is evident that there are more researchers who have used Subjective Norm, for example [59], [78], [82], [83], [1], [26], [85], [86], [87], [88], [89], [90], [91], [92], Experience in the internet & computer [59], [77], [81], [82], [84], [85], [93], [94], [95], [96], [97] Self-Efficacy [59], [83], [84], [85], [1], [71], [72], [73], [86], [95], [98], [99], [74], [97], Technical Support [59], [42], [73], [74], [83], [100], [101], [102] and Anxiety [72], [73],…”
Section: External Variables Of Tammentioning
confidence: 99%
“…Researcher [102] emphasized that Technical Support has no significant impact on Perceived Ease of Use while other researchers [55], [59], [74], [98], [100], [101] identified that Technical Support has a significant positive impact on Perceived Ease of Use. Thus, based on the above justification preposition 8 is formulated.…”
Section: Preposition 7: Technical Support Has An Impact On the Perceived Usefulnessmentioning
confidence: 99%
See 2 more Smart Citations
“…TAM's popularity was demonstrated by the number of articles and introductory papers [41] and [42]. [53], [69], [70], [57], [71], [61], [72][73][74][75][76] Self-Efficacy [35], [53], [58], [71], [61], [59], [55], [77], [78], [62], [74], [79][80][81], [76], Technical Support [35], [53], [29], [78], [81], [58], [82], [83], [84] and Anxiety [35], [77], [78], [69], [71], [61], [76], [85][86] [42]. There is a significant impact, so it is once Subjective Norm's collaboration was incorporated into the new model to examine a link between behavioral intention and social influence [36], [42].…”
Section: The Technology Acceptance Model (Tam)mentioning
confidence: 99%